The lowest level of tumor involvement is a significant prognostic factor for upper tract urothelial carcinoma after radical nephroureterectomy: A large retrospective cohort study - Huang, Ying-Che; Wang, Hung-Jen; Sung, Min-Tse; Chuang, Yao-Chi; Chen, Yen-Ta; Cheng, Yuan-Tso; Kang, Chih-Hsiung; Liu, Hui-Ying; Chang, Yin-Lun; Chiang, Po-Hui; Luo, Hao-Lun (Frontiers in Oncology, 2022)
Purpose To evaluate the prognostic impact of the lowest level of tumor location for upper tract urothelial carcinoma (UTUC) treated with radical nephroureterectomy (RNU). Materials and methods Data were collected from patients with UTUC treated with RNU (01/2005- 06/2020) at a single center in Taiwan. Patients were stratified by the lowest level of tumor location into three groups: renal pelvis only (RPO), above upper ureter (AUU), and below upper ureter (BUU). We compared characteristics between groups and examined the association of the lowest level of tumor involvement with intravesical recurrence (IVR), systemic metastasis (SM), and cancer-specific mortality (CSM). Results Overall, 1239 patients (542 RPO, 260 AUU, 437 BUU) were enrolled. Concurrent bladder cancer, multifocality, tumor architecture, lymphovascular invasion, carcinoma in situ, and variant histology were significantly different across different tumor locations. BUU had worse five-year intravesical recurrence (IVR), systemic metastasis (SM) and cancer-specific mortality (CSM) (p < 0.001, p = 0.056 and p = 0.13, respectively). In multivariable models, the lowest level of tumor involvement was an independent predictor of IVR (AUU hazard ratio (HR) = 1.52, p = 0.007; BUU HR = 1.75, p < 0.001), but only BUU was an independent predictor of SM (HR = 1.61, p = < 0.001) and CSM (HR = 1.51, p = 0.008). Conclusion The lowest level of tumor involvement in UTUC, especially BUU, was associated with a higher risk of IVR, SM and CSM. Assessment of the lowest level of tumor involvement after RNU may help identify patients who require more intensive follow-up.